A Lipiodol Pickering Emulsion Stabilized by Iron‐Doped Carbon Nanozymes for Liver Transarterial Chemoembolization - Xiancheng Xia; Yang Li; Rongkang Huang; Yuanbin Wang; Wenxuan Xiong; Hui Zhou; Min Li; Xidong Lin; Youchen Tang; Bo Zhang (Advanced Science)
Abstract Transarterial chemoembolization (TACE) utilizing a water‐in‐oil lipiodol emulsion is a preferable therapeutic strategy for advanced liver cancer in clinical practice. However, the low stability of the lipiodol emulsion and poor efficacy of chemotherapeutic drug seriously undermine the efficiency of TACE. Herein, a novel lobaplatin‐loaded lipiodol emulsion (denoted as ICN‐LPE) is developed by constructing a lipiodol Pickering emulsion (LPE) stabilized with iron‐doped carbon nanozymes (ICN) to mitigate the issue of lipiodol‐water separation. This novel emulsion not only solves the instability of conventional lipiodol emulsions, but also facilitates the sustained release of lobaplatin. More importantly, upon entry into tumor cells, ICN catalyze the generation of reactive oxygen species via the Fenton‐like reaction while simultaneously consuming intracellular glutathione, thereby inducing tumor cell death via chemodynamic therapy. By integrating chemotherapy and chemodynamic therapy, ICN‐LPE demonstrates a synergistic antitumor effect and effectively inhibits tumor growth in a rabbit liver tumor model. Therefore, our ICN‐LPE shows an appealing clinical application prospect for TACE.